EFFECT OF DIFFERENT EXTENDERS ON HYPO-OSMOTIC SWELLING OF DOG SEMEN PRESERVED AT 5° C - DAS, ARUNODAY; BISWAS, R K; DEKA, B C (The Indian Journal of Animal Reproduction, 2023)
The objective of the present study was to evaluate the preservability of different extenders for dogsemen on the basis of hypo-osmotic swelling test (HOST). Semen samples from three Labrador Retriever (LR) dogs were collected by digital manipulation method at weekly intervals. The first and second fractions of the ejaculates were collected combinedly in a single collection cup. The semen samples· were then extended @ 1 :4 in Tris-Egg Yolk- Citric Acid-Glucose (TEYCAG), Tris-Egg Yolk- Citric Acid-Fructose (TEYCAF) and Egg Yolk-Citrate-Glycine-Glucose (EYCGG) extenders by split sample technique and preserved at 5° C. The preserved semen was evaluated for HOST-reacted sperm at 24, 48, 72, 96 and 120 hours of preservation. The mean incidence of HOST- reacted sperm was 93.44 ± 1.92, 92.20 ± 1.72 and 85.65 ± 3.01 ; 87.99 ±4.35, 85.56 ± 3.82 and 75.34 ± 6.86; 85.03 ± 4.23, 82.25 ± 4.32 and 68.88 ± 7.46; 82.20 ± 4.42, 78.75 ±5.17 and 59.33 ± 5.10; and 79.51 ± 4.25, 70.00 ± 3.63 and 52.50 ± 3.71 per cent in TEYCAG, TEYCAFand EYCGG extenders at 24, 48, 72, 96 and 120 hours of preservation respectively. Analysis of variance revealed that the mean incidence of HOST-reacted sperm differed significantly (P
Keywords: Extenders; HOST-test; Dog semen; Preservation